Ethnobotany and ecology of plants of importance reproductive health: A case study of Subri River Forest Reserve in the Western Region of Ghana - Diame, Gertrude Lucky Aku (University of Cape Coast, 2007)
Ethnobotanical and ecological studies were carried out to take inventory of the species used by the inhabitants surrounding the Subri River Forest Reserve for reproductive health care and to assess the ecological status of woody plant species of this reserve. The study was carried out between November 2005 and December 2006. Medical ethnobotanical knowledge was gathered from 80 inhabitants in 25 communities using questionnaires. Reproductive health conditions were categorized into 19 major conditions, some of which included abortion, breast cancer, miscarriage and sexual impotence; and 7 corporeal or body systems. A total of 185 medicinal plants species, distributed in 60 families and 155 genera were cited. The most cited species was Gouania longipetala (4.23%). Of these 185 species, 72.97% were woody, while 27.03% were herbaceous. The most frequently employed plant part was barks (32.49 %), followed by roots (29.95%) and leaves (21.32%). Phytosociological studies on woody species with girth of at least 10 cm were undertaken in 50 circular plots of 0.1 ha, making a total of 5ha study area. A total of 128 species belonging to 104 genera and 45 families were encountered. The importance value indices of these species were generally low (0.28 to 20.09). Their distribution into Raunkiaer's frequency classes showed that 92.19% of the species were rare and none was common. There were high species diversity indices of Simpson (0.96) and Shannon-Weaver (4.00). Species evenness was also high (0.82). Only 57 (44.53%) of the woody species were cited for reproductive health conditions. The Relative Importance (RI), calculated from an ethnobotanical perspective, showed that approximately 28% of the 57 plant species were versatile. Alchornea cordifolia was the most versatile species for the reproductive health conditions. However, there was no significant (p>O.05) association between the RI and the phytosociological parameter values of the 57 woody medicinal species. Provisions of sustainable harvesting methods, adequate knowledge about forest management and cultivation among others, will ensure the conservation and sustainable use of these medicinal plants.
xiii,194p.:ill.
Keywords: River; MEDICINE::Surgery::Obstetrics and women's diseases::Reproductive health; Ghana